COMPARATIVE ANALYSIS OF CHECK-IN TECHNOLOGIES AT THE AIRPORT - Marintseva, Kristina (Proceedings of National Aviation University (archive), 2014)
The problem of check-in technologies at the airport is studied. The research is based on the experimental data obtained by method of observation check-in process at Boryspil airport (Kyiv, Ukraine). Distribution laws of waiting time and passenger service time at the check-in area are described. The method of dynamic opening and closing of check-in counter, which based on a model of the queueing theory, is proposed.